Penyuluhan Vulva Hygiene Dan Tata Laksana Vulvovaginitis Pada Pengemudi Ojek Online Di Wilayah Jabodetabek - Rully Ayu Nirmalasari; Lily Marliany Surjadi; Raditya Wratsangka (CV. Multi Kreasi Media, 2023)
Vulvovaginitis is a major gynecological disorder found in women of reproductive age. Various risk factors can increase the incidence of vaginitis, including occupational factors. Of the 50 female online motorcycle taxi drivers in the Jabodetabek area who had microbiological examination of vaginal secretions, 70% had vaginitis. The highest prevalence of infections found was due to bacterial vaginosis, and the majority of participants had tinea inguinalis. For this reason, this acounseling and treatment activity aims to increase knowledge about good vulvavaginal hygiene behavior, detect symptoms of vulvovaginitis and provide therapy and referral if these symptoms are found.